Two distinct channels of olfactory bulb output - Fukunaga, Izumi; Schaefer, Andreas T. (Neuron, 2012)
Summary: Rhythmic neural activity is a hallmark of brain function, used ubiquitously to structure neural information. In mammalian olfaction, repetitive sniffing sets the principal rhythm but little is known about its role in sensory coding. Here, we show that mitral and tufted cells, the two main classes of olfactory bulb projection neurons, tightly lock to this rhythm, but to opposing phases of the sniff cycle. This phase shift is established by local inhibition that selectively delays mitral cell activity. Furthermore, while tufted cell phase is unperturbed in response to purely excitatory odorants, mitral cell phase is advanced in a graded, stimulus-dependent manner. Thus, phase separation by inhibition forms the basis for two distinct channels of olfactory processing.